SINGLE-CENTER DESCRIPTIVE STATISTICAL ANALYSIS OF GLIAL TUMORS WITH REFERENCE TO GLIOBLASTOMAS - Zdravkovski, Panche; Ilievski, Boro; Rendevski, Vladimir; Chaparoski, Aleksandar; Filipche, Venko; Shuntov, Blagoj; Kocevski, Ivica; Stojkovski, Igor; Petrushevska, Gordana (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Gliomas are the most common primary intracranial brain neoplasms composing almost 80% of all cancerous brain tumours. Glioblastoma is the most common malignant brain tumour in the adult population and accounts in about 15% of all intracranial neoplasms. This observational analytical study gives a better overview of the current state of glial tumours in North Macedonia from 2021 to 2022 with special reference to glioblastomas. Epidemiological and statistical analysis of glial and other brain tumours in a specific time period with special reference to glioblastomas. This research is an observational statistical analysis that takes place on the Institute for Pathology in the Medical Faculty of ‘’Ss. Cyril and Methodius’’ University in Skopje using the digital data base of patients that had undergone surgery in the University Clinic of Neurosurgery and were diagnosed at the Institute of pathology during the time period 2021-2022. In the period from 2021 and 2022, at the Institute of pathology were diagnosed 106 (62%) glioblastomas out of which classic glioblastoma histomorphology confined 85 (80.19%) cases; 9 (8.49%) glioblastomas showed oligodendroglial component, 5 (4.72%) cases were gliosarcomas and 4 (3.77%) cases were diagnosed as giant cell glioblastomas. Three (2.83%) cases showed glioblastoma histomorphology with radionecrosis. When it comes to global statistics, we can conclude that Republic of North Macedonia follows the global trends regarding the incidence of glioblastoma associated with gender. Our results show that glioblastoma is more prevalent in males than females with the ratio male to female being 1.2:1, and this tumour is more prevalent in patients older than 55 years with the average age of diagnosis being 61 years. The results of this descriptive statistical analysis show that glial tumours, especially glioblastomas as most prevalent malignant tumour type deserves greater scientific attention which beside the impact on their diagnostic complexity, will expand the knowledge of this pathology field and strongly reflect on future scientific and diagnostic work. Keywords: Glioblastoma, glial tumors, statistics, analyzis, epidemiology.